"I Was a Muslim, But Now I Am a Christian": Preaching, Legitimation, and Identity Management in a Southern Evangelical Church. Issue 2 (4th August 2016) - Marti, Gerardo
Abstract : Established in 2005, "Life" is a suburban, nondenominational, evangelical church in Charlotte, North Carolina, with an almost entirely white membership, yet the lead pastor is an immigrant from the Middle East. As an ex‐Muslim ethnic Pakistani who was born and raised in Kuwait, Pastor Sameer Khalid does not "fit" into southern culture, and he did not convert to Christianity until he was enrolled in college in the United States. Ethnographic data from 14 months of fieldwork reveal how Pastor Sameer uses weekly sermons to negotiate racialized stigmas, emphasize his common religious identity with the congregation, and make his immigrant background a distinctive religious resource for the church. More specifically, while all pastors require legitimation of their charismatic authority, this research focuses on the dynamics of performance through preaching within the Sunday morning services of this congregation, a performance that negotiates this lead pastor's ethnic and religious identities and accentuates his strategic use of institutionalized evangelical narratives to subvert Islamophobic threats and buttress legitimation of his pastoral identity.